PENGARUH PENERAPAN MANAJEMEN STRATEGIS DAN KOMPETENSI KEPALA SEKOLAH TERHADAP PENCAPAIAN STANDAR PENGELOLAAN PENDIDIKAN DI SMA NEGERI 19 MAKASSAR - DJ, Muh Yusuf; Syamsudduha, St.; Rapi, Muh. (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The objectives of this study are: First, describe the application of strategic management, the competence of principals, and describe the application of educational management standards; the second examines the influence of strategic management and school principals' competencies on achieving educational management standards in Makassar 19 Public High School. This type of research is survey research. The total population is 579, and 121 samples are taken. Data collection uses questionnaire and documentation techniques. The data analysis uses descriptive statistics and inferential statistics. The results of this study indicate that, strategic management and competency of school principals jointly have a positive and significant effect on the achievement of education management standards in SMA 19 Makassar with a regression equation Y = 50,450 + 0.467X1 + 0.216X2 and the coefficient of determination of 0.209 so that the achievement of educational management standards 20.9% is determined by strategic management together with the competency of principals and 79.1% is determined by other factors not included in this research area.